Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique